American Dark Romanticism Characteristics in Lenore - Khoe, Yohana Harsono; Ekawati Marhaenny Dukut (Soegijapranata Catholic University, 2020)
Abstract: Analyzing the words and phrases used in Edgar Allan Poe’s Lenore can portray the characteristics of the Dark Romanticism era of the United States of America, which consist of 1) imagination, 2) nature, 3) symbolism and myth, 4) intuition and subjectivity, and 5) individualism. Through a biographical and sociological approach, it was found that there were words in Lenore that support the Dark Romanticism characteristics. The dark, creepy, gloomy, and dreary, words that hint the feeling of Poe’s uneasiness while living a dark and difficult life in the 1800s in America were “no tear… weep now”, “grief and groan”, “Stygian River”, “golden brown”, “Hope”, “Peccavimus”, “Lenore” and “death”.Key words: Edgar Allan Poe, poem, romanticism era, dark romanticism, LenoreAbstrak: Menganalisis kata-kata yang digunakan oleh Edgar Allan Poe dalam puisinya Lenore dapat memperlihatkan karakteristik dari masa Dark Romanticism yang dialami oleh negara Amerika Serikat, yaitu adanya karakteristik: 1) imagination, 2) nature, 3) symbolism and myth, 4) intuition and subjectivity, dan 5) individualism. Melalui pendekatan biografi dan sosiologi maka ditemukan beberapa kosa kata dari puisi Lenore yang mendukung masa Dark Romanticism yang dipenuhi dengan lingkungan yang gelap, menyeramkan, dan menyedihkan itu. Beberapa kosa kata yang menandakan ketidaknyamanan Poe dalam melalui kehidupannya pada tahun 1800an di Amerika Serikat adalah kata “no tear… weep now”, “grief and groan”, “Stygian River”, “golden brown”, “Hope”, “Peccavimus”, “Lenore” and “death”.Kata kunci: Edgar Allan Poe, puisi, era romantisisme, dark romanticism, Lenore